IMPLEMENTASI MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS III SD - Nur Himatul Munawaroh Hima; Kartinah; Fine Reffiane (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the increase in student learning outcomes after implementing thematic learning using the Problem-Based Instruction Model. This research is a class action research (CAR) which was carried out for two cycles. The subjects of this study were 28 grade III students at SDN Peterongan Semarang City. Collecting data using observation techniques and learning achievement tests. The collected data were analyzed by calculating the percentage of learning success and the average value achieved by students. The results showed that the thematic learning outcomes through the application of the Problem-Based Instruction (PBI) learning model in class III students in semester II of the 2022/2023 school year were stated to increase, this was evidenced by an increase in the average class III student learning outcomes in cycle I by 72, 85 and in cycle II to 80.35. Thus, the application of the Problem-Based Instruction (PBI) learning model to third-grade students at SDN Peterongan Semarang City can improve thematic learning outcomes.